Dynamic Properties of the Solow Model with Increasing or Decreasing Population and Time-to-Build Technology - Luca Guerrini; Mauro Sodini (Abstract and Applied Analysis)
We introduce a time-to-build technology in a Solow model with nonconstant population. Our analysis shows that the population dynamics may be a source of stability switches and Hopf bifurcations. The analytical results are obtained using the recent technique introduced by Beretta and Kuang (2002) in the studying of delayed differential equations with delay-dependent coefficients in characteristic equation. Numerical simulations are performed in order to illustrate the main dynamic features of the model.